2008
DOI: 10.1037/0096-1523.34.2.475
|View full text |Cite
|
Sign up to set email alerts
|

The role of visual occlusion in altitude maintenance during simulated flight.

Abstract: The use of visual occlusion as a cue to altitude maintenance in low-altitude flight (LAF) was investigated. The extent to which the ground surface is occluded by 3-D objects varies with altitude and depends on the height, radius, and density of the objects. Participants attempted to maintain a constant altitude during simulated flight over an undulating terrain with trees of various heights, radii, and densities. As would be predicted if participants used occlusion, root-mean-square error was related to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Performance Similar to previous studies studies [10,19,20] root mean square error (RMSE) of the vertical deviation from the ideal 3 • glideslope was used as the performance metric. In X-Plane, one glideslope dot represents a 0.28 • error.…”
Section: Methodsmentioning
confidence: 99%
“…Performance Similar to previous studies studies [10,19,20] root mean square error (RMSE) of the vertical deviation from the ideal 3 • glideslope was used as the performance metric. In X-Plane, one glideslope dot represents a 0.28 • error.…”
Section: Methodsmentioning
confidence: 99%
“…The observed flightpath deviations show similar amplitudes compared to other flight simulator studies (Ebbatson et al 2010;Haslbeck and Hörmann 2016), thus indicating that the occlusion conditions in this study did affect the participants but did not lead to a complete failure in the manual flying task (Table 6). Thus, occlusion appears as an approach to generate valid data to analyze pilots' performance under conditions of restricted visual resources (see Gray et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Occlusion was successfully used to evaluate operator performance and estimate attentional demand not only in the automotive domain, but also in other fields involving highly skilled performance such as aviation (Milgram 1987). Gray et al (2008) have taken the occlusion paradigm in a different way: in a manual fine-motor flying task to maintain a constant altitude, they occluded the ground surface by 3D objects. In the current study, the benefit compared to more intense techniques such as eye tracking is that occlusion allows for a very selective and controlled manipulation of an operator's visual perception, which is a very important channel for many psychomotor control tasks (Helleberg and Wickens 2003;Gelau and Krems 2004) with a clear distinction between the information a subject should receive and the information to be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Altitude change detection was good even when there was no texture on the ground surface suggesting that changing object size was a reliable visual cue to altitude maintenance. More recently it has been shown that the presence of 3D objects provides motion parallax (Covas, Patterson, Geri, Akhtar, Pierce, & Dyre, 2005) and visual occlusion (Gray, Geri, Akhtar, & Covas, 2007) cues that can be used to maintain altitude.…”
Section: Introductionmentioning
confidence: 99%